Anogenital warts in children: sexual abuse or unintentional contamination? Verrugas anogenitais na infância: abuso sexual ou contaminação não-intencional? - Lisieux Eyer de Jesus; Oscar Luís Lima e Cirne Neto; Leila Maria Monteiro do Nascimento; Rejane Costa Araújo; Andréa Agostinho Baptista (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
Anogenital warts (AGW) were recently recognized in children, and their significance as an index of childhood sexual abuse is controversial. We report our transdisciplinary approach (including a pediatric surgeon, psychologist, social worker, ethics expert, and occasionally law enforcement agents) and its results in a group of 17 children with AGW treated at the public pediatric referral hospital in Rio de Janeiro, Brazil, during a 3-year period (1996-1999). All children were treated by electrocauterization of the warts, tested for other STDs, and submitted to perineal examination under anesthesia. Families received psycho-social counseling as necessary and cases were referred to child protection and law enforcement agents when indicated according to Brazilian legislation. We identified a high incidence of sexual abuse (8 children, 5/7 > 5 years old), with 3 patients inconclusive as to sexual abuse and 7 cases of perinatal transmission (5/8 < 4 years old). We conclude that AGW are indeed a strong sign of suspicion for sexual abuse in children, especially but not exclusively > 5 years of age. However, strong support and a transdisciplinary approach to the children and their families is necessary to identify it. Verrugas anogenitais (VAG) são de reconhecimento recente na criança e seu significado como sinal de abuso sexual é controverso. Relatamos nossa abordagem multidisciplinar (cirurgião pediatra, psicólogo, assistente social, conselheiro de ética e eventualmente agente legal) e seus resultados, num grupo de 17 crianças com VAG tratadas em um hospital público de referência no Rio de Janeiro, Brasil, em um período de três anos (1996-1999). Todos foram tratados por eletrocoagulação das verrugas, testadas para outras DSTs, e submetidos a um exame perineal sob anestesia. Todas as famílias foram amparadas pelos assistentes sociais e psicólogos na medida do necessário, e casos de violência comprovada ou suspeita foram encaminhados de acordo com as leis brasileiras. Foi descoberta uma alta incidência de abuso sexual previamente insuspeito (oito crianças, 5/7 dos maiores de cinco anos de idade), três casos foram inconclusivos quanto à presença de abuso sexual e sete foram considerados transmissão não agressiva (5/8 dos menores de quatro anos de idade). Concluímos que VAG em crianças são muito sugestivas de abuso sexual, em especial, mas não exclusivamente, em idade escolar, mas é necessário amplo suporte e abordagem multidisciplinar para evidenciar o abuso ocorrido.